FORMATION OF CREATIVE COMPETENCE IN FUTURE TEACHERS - Fuzailova Gavkhar Siddikovna (Journals Park Publishing, 2023)
The purpose of the study is to reveal the impact of innovative technologies on developing creative activity of future specialists. In the course of experimental work, the main innovative methods to promote the formation of students’ creativity were identified, the practice of using case-method and features of the case-forming technology to form students’ creativity were described.
Keywords: innovation; case method; creativity; creative thinking and social activism of future specialists.